Scenario of Scleractinian Larva Dispersal in Sulawesi Waters From A Hydrodynamic Modeling Perspective - Umar, Widyastuti; Jompa, Jamaluddin; Pata, Mustono (Hasanuddin University, 2023)
Scleractinian coral such as Lobophyllia corymbosa that reproduce by external fertilization have an extended planktonic phase in their life cycle during which they